Effect of long-term individual cognitive stimulation intervention for people with mild neurocognitive disorder - Otero, Patricia (2021)
Introduction. Cognitive stimulation may be beneficial in slowing the progression of mild neurocognitive disorder (NCD), but the results of existing research are inconsistent. Furthermore, there are no long-term interventions nor individual (one-on-one) interventions applied by professionals. Objetive. The aim of this study was to assess the efficacy of a long-term individual cognitive stimulation intervention on people with mild NCD. Patients and methods. A pre-post test design with a non-equivalent control group was conducted. A total of 82 participants with mild NCD were assigned to a cognitive stimulation intervention group or to a control group. The intervention consisted of 88 individual format sessions of approximately 45 minutes, twice per week. Independent evaluators assessed cognition, depressive symptomatology and autonomy level in activities of daily living at preintervention, intra-intervention (6 months) and post-intervention (12 months). Results. At intra- and post-intervention, significant improvement on cognition and depressive symptomatology in the intervention group compared to the control group were found. Younger participants and those with better cognitive function and status in pre-intervention achieved better results. Adherence to the intervention was high. Conclusions. Results suggest the efficacy of long-term individual cognitive intervention in people with mild NCD, which could delay the progression towards a major NCD.